Effect of essential oils extracted from Chromolaena odorata (L.) R. M. King & H. Rob. against Macrotermes carbonarius (Hagen, 1858) and Globertermes sulphurous (Haviland, 1898) - Fauziah Abdullah,; Muhamed Musthafa, Muneeb; Mohd Shukri Mohd Sabri,; Nor Hidayah Mamat,; Rafidah Isa,; Sri Nurestri Abdul Malek,; Lee, Guan Sern (Pusat Sistematik Serangga ,UKM, 2020)
Chromolaena odorata was examined for insecticidal properties against termites Macrotermes carbonarius and Globertermes sulphurous, where G. sulphureus and M. carbonarius workers and soldier colonies were collected from selected areas of Kuala Lumpur, Selangor and Pahang, respectively. Extracted essential oils were tested on Macrotermes carbonarius and Globertermes sulphurous worker and soldier termites. The results of the preliminary bioassay were subjected with ANOVA and Probit analysis to determine values of LC50. Results showed that the essential oil of stem and leaves of Chromolaena odorata displayed lethal effects on tested termites. Probit analysis showed that there was a significant increase in termite mortality, when treated with leave and stem of C. odarata oil. Meanwhile, M. carbonarius soldier was not showed any significant different in both stem and leave of C. odorata oil. In fumigant assays, LC50 value for M. carbonarius worker was 44.7 ppm after 24 hours of treatment while for worker G. sulphureus worker the LC50 was 1118.92 ppm. The soldiers of M. carbonarius were more susceptible than soldiers of G. sulphureus. The LC50 for soldier M. carbonarius was 778.4 ppm while the LC50 was 1568.1 ppm for soldier G. sulphureus at 24 hours. Analysis using Gas chromatography–Flame Ionization Detector (GCFID) and Gas chromatography–mass spectrometry (GCMS) revealed number of potential compounds responsible for the mortality of termites such as -pinene, germacrene D and βpinene etc. In general, the GCMS should be preferred for qualitative analysis (identification of molecules when in doubt), and the GCFID for quantitative analysis (determining the percentage of each compound in an essential oil). Both stems and leaves of C. odonata essential oil could be used as an alternative protectant for wood and wood products against termites.